The Making of National Money : Territorial Currencies in Historical Perspective - Helleiner, Eric, 1963- (Book collections on Project MUSE., 2003)
Why should each country have its own exclusive currency? Eric Helleiner offers a fascinating and unique perspective on this question in his accessible history of the origins of national money. Our contemporary understandings of national currency are, Helleiner shows, surprisingly recent. Based on standardized technologies of production and extraction, territorially exclusive national currencies emerged for the first time only during the nineteenth century. This major change involved a narrow definition of legal tender and the exclusion of tokens of value issued outside the national territory. "Territorial currencies" rapidly became bound up with the rise of national markets, and money reflected basic questions of national identity and self-presentation: In what way should money be managed to serve national goals? Whose pictures should go on the banknotes? Helleiner draws out the potent implications of this largely unknown history for today's context. Territorial currencies face challenges from many monetary innovations-the creation of the euro, dollarization, the spread of local currencies, and the prospect of privately issued electronic currencies. While these challenges are dramatic, the author argues that their significance should not be overstated. Even in their short historical life, territorial currencies have never been as dominant as conventional wisdom suggests. The future of this kind of currency, Helleiner contends, depends on political struggles across the globe, struggles that echo those at the birth of national money